2014
DOI: 10.1155/2014/704398
|View full text |Cite
|
Sign up to set email alerts
|

Six-Digit CPK and Mildly Affected Renal Function in McArdle Disease

Abstract: A previously healthy, white 12-year-old girl presented with diffuse body aches and poor perfusion. She developed severe respiratory failure and marked rhabdomyolysis and was mechanically ventilated. Although her CPK peaked at 500,000 IU/L, her renal function was mildly affected and her creatinine did not exceed the 0.8 mg/dL. The rhabdomyolysis was gradually resolved following aggressive fluid hydration. The patient did not require dialysis and made a complete recovery. Genetic studies revealed the diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…2 Although there is no established cutoff levels, a concentration 5 to 10 times higher than the upper limit of normal reference range (ie, 500-1000 U/L) is commonly used. 2,6 Other laboratory indicators include serum and urine myoglobin concentrations that may be useful but not essential for the diagnosis. 2 The most common complication of rhabdomyolysis is kidney damage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Although there is no established cutoff levels, a concentration 5 to 10 times higher than the upper limit of normal reference range (ie, 500-1000 U/L) is commonly used. 2,6 Other laboratory indicators include serum and urine myoglobin concentrations that may be useful but not essential for the diagnosis. 2 The most common complication of rhabdomyolysis is kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Other laboratory indicators include serum and urine myoglobin concentrations that may be useful but not essential for the diagnosis. 2 The most common complication of rhabdomyolysis is kidney damage. 1,2 In recent large pediatric studies reported by Mannix et al 7 and Wu et al, 8 it was shown that the rate of acute renal failure in the pediatric patients with rhabdomyolysis ranged from 5% to 8.7%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations